Archival Sources for Legal Biography at the Institute of Advanced Legal Studies. (12th March 2014) - Dawson, Elizabeth
Abstract: Elizabeth Dawson's article outlines archival sources for legal biography held at the Institute of Advanced Legal Studies, focussing on primary sources of information on individuals, including the Law Society and Bar Examination results. It also summarises additional sources which provide biographical information on legal practitioners and scholars eg. the archives of The Society of Legal Scholars and the Council of Legal Education, IALS institutional archives, The Bar Council, The International Law Association and academic membership associations. The article also provides guidance to researchers on using the IALS Archive, and advice on using related external archival sources.